Germline variation in inflammation-related pathways and risk of Barrett's oesophagus and oesophageal adenocarcinoma. Issue 10 (2nd August 2016) - Buas, Matthew F; He, Qianchuan; Johnson, Lisa G; Onstad, Lynn; Levine, David M; Thrift, Aaron P; Gharahkhani, Puya; Palles, Claire; Lagergren, Jesper; Fitzgerald, Rebecca C; Ye, Weimin; Caldas, Carlos; et al.
Abstract : Objective: Oesophageal adenocarcinoma (OA) incidence has risen sharply in Western countries over recent decades. Local and systemic inflammation is considered an important contributor to OA pathogenesis. Established risk factors for OA and its precursor, Barrett's oesophagus (BE), include symptomatic reflux, obesity and smoking. The role of inherited genetic susceptibility remains an area of active investigation. Here, we explore whether germline variation related to inflammatory processes influences susceptibility to BE/OA. Design: We used data from a genomewide association study of 2515 OA cases, 3295 BE cases and 3207 controls. Our analysis included 7863 single-nucleotide polymorphisms (SNPs) in 449 genes assigned to five pathways: cyclooxygenase (COX), cytokine signalling, oxidative stress, human leucocyte antigen and nuclear factor-κB. A principal components-based analytic framework was employed to evaluate pathway-level and gene-level associations with disease risk. Results: We identified a significant signal for the COX pathway in relation to BE risk (p=0.0059, false discovery rate q=0.03), and in gene-level analyses found an association with microsomal glutathione-S-transferase 1 ( MGST1 ); (p=0.0005, q=0.005). Assessment of 36 MGST1 SNPs identified 14 variants associated with elevated BE risk (q<0.05). Four of these were subsequently confirmed (p<5.5×10 −5 ) in a meta-analysis encompassing an independent set of 1851 BE cases and 3496 controls, and are known strong expression quantitative trait loci for MGST1 . Three such variants were associated with similar elevations in OA risk. Conclusions: This study provides the most comprehensive evaluation of inflammation-related germline variation in relation to risk of BE/OA and suggests that variants in MGST1 influence disease susceptibility.